Сутність та зміст функцій територіальних управлінь Державного бюро розслідувань - Богданов, Р. І.; Bohdanov, R. I. (Наше право. - 2023. - № 3. - С. 256-261, 2023)
Здійснено аналіз норм чинного законодавства, яке регулює діяльність Державного бюро розслідувань взагалі та його територіальних управлінь, зокрема. Наголошено, що функції територіальних управлінь слід охарактеризувати як спрямовані на виконання завдань ДБР напрямки діяльності, види впливу на суспільні правовідносини, обумовлені колом їх компетенції. Відповідні функції запропоновано поділити на дві групи: загальні та спеціальні.

It is argued that the functions of territorial administrations should be characterized as areas of activity aimed at the fulfillment of the tasks of the SRB, types of influence on social legal relations, determined by the scope of their competence. The functions are realized through the powers defined by the law. It was emphasized that the functions of the territorial administrations of the SBI should be divided into two groups: general and special. It is noted that the general functions are due to the affiliation of the SBI to the law enforcement body. Such functions are proposed to include: warning-educational (preventive), analyticalinformational (analysis of received information, search for patterns, including the causes and conditions of committing crimes in one or another area for the purpose of their prevention), protective (protection of violations of the law defined procedure for the implementation of official activities through the implementation of operative-search and investigative measures), organizational-normative (regarding the provision of the organization of the functioning of the territorial administration on the basis of streamlining the activities of its structural units, determining the order of interaction between them). It is argued that the special functions stem from the special assignment of the territorial offices of the SBI in relation to the fight against crimes assigned to their competence within certain administrativeterritorial units. Special functions include: formation of a responsible attitude to official activity, as they ensure the inevitability of the negative consequences of crimes committed in the course of its performance; support of trust in the authorities, because the sphere of activity of the SBI extends precisely to those crimes related to the violation of official duties of persons endowed with authority, so the effective operation of the departments demonstrates the lack of interest of the authorities in their presence.

Осуществлен анализ норм действующего законодательства, регулирующего деятельность Государственного бюро расследований вообще и его территориальных управлений, в часности. Отмечено, что функции территориальных управлений следует охарактеризовать как направленные на выполнение задач ДБР направления деятельности, виды влияния на общественное правоотношение, определяемые кругом их компетенции. Функции предложено разделить на две группы: общие и специальные.
Keywords: територіальні управління; Державне бюро розслідувань; функції; напрями діяльності; territorial administration; State Bureau of Investigation; functions; areas of activity; территориальные управления; Государственное бюро расследований; функции; направления деятельности